2016
DOI: 10.1371/journal.pone.0166147
|View full text |Cite
|
Sign up to set email alerts
|

SLC7A5 Functions as a Downstream Target Modulated by CRKL in Metastasis Process of Gastric Cancer SGC-7901 Cells

Abstract: SLC7A5, who is also named LAT-1, has been validated as a promoter regulated by miRNA-126 in our previous research for gastric cancer cells. However, the mechanisms driving SLC7A5 to affect the bio-function of gastric cancer cells are unclear, remaining us lots of to elucidate. The aim of this study is to investigate the regulating effect of CRKL, one of the critical genes involving with gastric cancer progression, on SLC7A5 expression. By studying the gastric cancer cell lines and clinical pathological specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…3A). Indeed, previous immunohistochemistry (IHC) studies found that both SLC1A5 and SLC7A5 were up-regulated in colon cancer cells (Huang et al 2014;Wang et al 2016;Toda et al 2017).…”
Section: Myc Promotes the Expression Of Trp Transporters And Enzymes mentioning
confidence: 99%
“…3A). Indeed, previous immunohistochemistry (IHC) studies found that both SLC1A5 and SLC7A5 were up-regulated in colon cancer cells (Huang et al 2014;Wang et al 2016;Toda et al 2017).…”
Section: Myc Promotes the Expression Of Trp Transporters And Enzymes mentioning
confidence: 99%
“…GSE1 is positively associated with many clinicopathological features, namely lymph node metastasis, clinical stage, depth of invasion and histological grade and LAT1 appears to mediate its functions and to be positively regulated by GSE1 [ 75 ]. Wang et al [ 47 ] identified LAT1 as a downstream target of the CRK-like (CRKL) protein, a promoter of gastric cancer. Depletion of CRKL in a gastric cancer cell line resulted in impairment of SLC7A5 expression and suppression of cell motility [ 47 ].…”
Section: Asct2 and Lat1: Their Contribution To The Hallmarks Of Camentioning
confidence: 99%
“…Wang et al [ 47 ] identified LAT1 as a downstream target of the CRK-like (CRKL) protein, a promoter of gastric cancer. Depletion of CRKL in a gastric cancer cell line resulted in impairment of SLC7A5 expression and suppression of cell motility [ 47 ].…”
Section: Asct2 and Lat1: Their Contribution To The Hallmarks Of Camentioning
confidence: 99%
“…LAT1 and LAT2 require a complex formation with 4F2hc (SLC3A2), also known as CD98, for their functional expression 15 . LAT1 and 4F2hc have been reported to be up‐regulated and play an important role in cancer progression in various tumors such as head and neck squamous cell carcinoma,prostate, breast, colon, gastric, and bladder cancers,cholangiocarcinoma,and endometrioid endometrial carcinoma 19‐25 . The up‐regulation of the LAT1‐4F2hc complex supports cancer progression by enhancing the ability to import leucine into the cells, hence triggering the mechanistic target of rapamycin (mTOR) signaling pathway, which is important in cell growth and proliferation 26 .…”
Section: Introductionmentioning
confidence: 99%